The impact of the Syrian War on the Cognitive Development of Children in Al-Zaatari Camp, Jordan: A Comparative Analysis - Luthfiah Mawar; M. Agung Rahmadi; Rasya Ramadhan; Annisa Br Bangun; Emia Enjelita; Helsa Nasution; Nurzahara Sihombing; Nafiza Rizky Ramadhani Lubis (Jurnal Medika Nusantara, 2025)
This meta-analysis sistematically examines the impact of war exposure on the cognitive development of Syrian refugee children aged 5 to 17 years residing in Al-Zaatari Camp, Jordan, by synthesizing data from 47 longitudinal and quasi-longitudinal studies with a total sample of 8,426 participants published between 2011 and 2024. The results indicate consistent and statistically significant cognitive impairments across domains, marked by a lower average IQ score of 11.2 points compared with non-refugee Syrian children (d = -0.78, 95% CI [-0.92, -0.64]). Significant declines were also identified in working memory capacity (beta = -0.43, p < 0.001), accompanied by deficits in executive functioning encompassing attention (d = -0.66), inhibitory control (d = -0.59), and cognitive flexibility (d = -0.71). Duration of displacement was moderately and negatively correlated with cognitive performance (r = -0.38, p < 0.001). Children who experienced direct exposure to war-related trauma (n = 3,241) demonstrated more severe impairment (M = -1.24 SD) compared with those exposed indirectly (n = 5,185, M = -0.86 SD). These findings extend the results of Sirin and Sirin & Rogers-Sirin (2015) and Caparos (2022), while uniquely identifying a critical period for intervention effectiveness: early intervention within 6 months of displacement yielded better outcomes (d = 0.45) than delayed intervention (d = 0.21). This study presents the first comprehensive longitudinal meta-analysis to map trajectories of child cognitive development within the refugee camp context and to establish an empirically grounded temporal window for the most effective intervention